(untitled) (Indian Journal of Experimental Biology (IJEB), 2021)
Beetroot stalks are regarded as agroindustrial waste, despite their nutritious and colourant characteristics. The pigments found in beetroot waste stalks were extracted using an ultrasonication approach in this investigation. Multiple regression analysis was used to investigate and assess the individual and interaction effects of power intensity, solid-solvent ratio, and sonication period on the betalains. Under optimal conditions (power intensity of 79.801 W/cm2, solid-solvent ratio of 22.4 g/ml, and sonication time of 26.7 min), the maximum betacyanin (3 mg/g) and betaxanthin (4.36 mg/g) were achieved. All responses of betalains extracted from beetroot waste stalks showed a significant (P <0.05) influence of process factors. It was also revealed in the study that ultrasound assisted extraction had actual yield of betalains (betacyanin, 2.92 mg/g and betaxanthin 4.27 mg/g), total phenolic content (69.74 mg GAE/g), as well as superior antioxidant activity (76.32%), than traditional techniques, under optimal conditions of independent process variables.